The research of Turkish terminology - Begimova, G. (Journal of Oriental Studies, 2016)
In this thesis we are going through the way of researching terminology formation, and the opinions of scholars about the terminologyon Turkish language linguistics. Also in this thesis we are looking at the history and present of Turkish terminology.